EFFECTS OF CONTROL AND AUTONOMY TO THE MANAGEMENT EFFICIENCY OF THE STATE OWNED ENTERPRISE - JURKONIS, LIUDAS (Politologija, 2012)
Based on the international review of SOE’s management practice and appropriate academical literature review, the paper seeks to explain and summarise main determinants of SOE performance efficiency. Specific case of Lithuania and / or other post-soviet countries have not be analysed in depth. Therefore, elements of SOE performance management are being analysed in this paper to understand the relations between SOE and its shareholder (state / government), SOE profitability and its contribution to the budget, quality of SOE services and production, the level of public and state interest to be included into the performance indicators of the specific SOE (e.g., in cases of natural monopolies and / or strategic interests of the state). Accordingly, as per main paradigms of public administration (including the analysis of traditional bureaucratic system, new public management (NPM) and post-NPM) SOE performance efficiency is being analysed via control or management autonomy concepts. Based on the analysis of best practices, summarised SOE management experiences of OECD countries, it is seen that the control of the state is being influenced via regulative and / or strategic resource management decisions. On the other hand, the autonomy of SOE is mainly related to the economical results (e.g., strong economical performance will increase the autonomy of SOE), market environment SOE is working in (e.g., high level of competition will require bigger autonomy of SOE), other factors (e.g., reputation of the executive managers of the SOE). Thus, analytical model (set of determining factors) which could be applied for the analysis of Lithuanian SOE management reform and its impact is being presented below: (i) External environment (political, social, competitive environment); (ii) Level of managerial autonomy (in the areas of strategic, market, financial, operational management); (iii) Public visibility via the number of customers, nature of services / goods provided by the company; (iv) Performance and economical efficiency (size of the company, revenue generated). The biggest challenge of the presented model is that factors identified above are interdependently related. However, despite this challenge, in further researches this model will be tested on the base of Lithuanian SOE’s seeking (1) to understand the actual level of influence of the above mentioned factors to the management efficiency of Lithuanian SOEs, (2) adapt and improve the model based on the empirical evidence of the research.